Popular Music in Singapore: Exploring Local Cultures, Global Resources, and Regional Identities - Kong, Lily (Institutional Knowledge at Singapore Management University, 1996)
As an area of geographical inquiry, popular music has not been explored to any large extent. Where writings exist, they are somewhat divorced from the recent theoretical and methodological questions which have rejuvenated social and cultural geography. In this paper one arena which geographers can develop in their analysis of popular music, namely, the exploration of local influences and global forces in the production of music, is focused upon. In analysing the music of Dick Lee, a Singaporean artiste, I illustrate how music is an expression of local/national influences. At the same time I discuss how Lee's music is also reflective of the power of globalising forces, illustrating the ways in which local resources intersect with global resources in a process of transculturation. Then I discuss the ways in which musical analysis offers a handle on larger political, economic, and sociocultural developments in Asia. Lee's search for a regional sound parallels the shift in many other spheres of Asian existence whereby a new cultural assertiveness has emerged, founded on the notion of Asian values and an 'Asian Way'.